2013
DOI: 10.12957/jbrastele.2013.8630
|View full text |Cite
|
Sign up to set email alerts
|

O Uso De Tecnologias De Informação E Comunicação Na Área Da Nutrição

Abstract: Resumo As tecnologias de informação e comunicação (TIC) apresentam o potencial de melhorar a gestão da informação, o acesso a serviços de saúde, a qualidade do cuidado prestado, a continuidade dos serviços, e a contenção de custos. Além disso, fornecem uma oportunidade singular para a promoção de estilos de vida saudáveis e valorização de iniciativas de políticas de saúde pública, atingindo simultaneamente um grande público. O objetivo do presente estudo foi revisar as experiências do uso das TIC na área da Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 2 publications
0
5
0
9
Order By: Relevance
“…Information and communication technologies are defined as those that assist the collection, processing, storage and exchange of information by electronic transmission. In health, these technologies enable the promotion of a healthy lifestyle, examples being electronic records, telehealth services, health information networks, tools that health professionals use and that support clinical decision making, and Internet-based technologies and services ( 1 ) .…”
mentioning
confidence: 99%
“…Information and communication technologies are defined as those that assist the collection, processing, storage and exchange of information by electronic transmission. In health, these technologies enable the promotion of a healthy lifestyle, examples being electronic records, telehealth services, health information networks, tools that health professionals use and that support clinical decision making, and Internet-based technologies and services ( 1 ) .…”
mentioning
confidence: 99%
“…Nesse sentido, diversos softwares para todas as áreas da saúde estão sendo criados e/ou aperfeiçoados. A utilização de tecnologia digital para cuidados em saúde constitui um importante recurso para auxiliar profissionais e indivíduos, sendo uma potencial ferramenta nas práticas médicas e de saúde pública, na medida em que colabora para a melhoria da gestão da informação, o acesso aos serviços, a qualidade do cuidado prestado e a contenção de custos (Curioni et al, 2013),além de possibilitar uma oportunidade singular para a promoção de estilo de vida saudável, o tratamento e a prevenção de doenças crônicas (Guillén et al, 2009). O uso de tecnologias informatizadas tem sua incorporação emergente e já são reconhecidas na literatura como uma ferramenta que otimiza o processo de gerenciamento, cuidado, ensino e pesquisa, estando diretamente relacionada com a melhora da qualidade dos serviços de saúde prestados (Goyatá et al, 2012;Queiroz et al, 2012).…”
Section: )unclassified
“…Consequently, a great number of patients may be reached with a relatively low cost, contributing to consultation attendance, adherence to follow-up, and clarification of doubts, thus bringing patient safety regarding nutrition. 8 The results from one study carried out in hospitals in the state of Michigan that evaluated safety culture and surgical complication rates showed that safety perception varies significantly according to each professional involved in the process and is not only about the surgical procedure, but also the quality of services provided, information availability, care, and communication with the health team. 9 Communication technologies may contribute significantly to this safety process and, consequently, when understanding the meaning of communication technologies and the personal reality of patients, it is possible to plan nutritionists' performance, seeking for more empathy and better relationship between professionals and patients.…”
Section: Introductionmentioning
confidence: 99%